CRISPR Technology in Bacterial Gene Editing and Therapy - Qassem Jawad Aijma; Hiba Qais Salman; Abdulrahman Mahmoud Mohammed; Hawraa Hazim Salim; Duaa Hani Obed (American Journal of Biology and Natural Sciences, 2024)
CRISPR technology is a part of a defense system found in bacteria and archaea that is used to destroy the DNA of foreign pathogens. A segment of DNA from the pathogen is incorporated into the bacteria’s DNA in between repeats of palindromic sequences, and enzymes transcribe these encoded repeat elements and use the RNA molecules as a guide to finding and destroying the DNA. The system is surprisingly malleable and has been repurposed for many uses, including gene editing of a wide variety of organisms. Bacteria protect themselves by putting a piece of an invading virus’s DNA inside a CRISPR cassette, essentially making themselves a wanted poster and keeping it in their genome so that more of the organisms can use it. One of the proteins made by the bacteria reads the DNA sequence from the wanted poster, and when the pathogen returns, it pairs to the DNA sequence and destroys it. However, the bacteria have also made a few small changes in the repeated DNA sequences over time to prevent the bacteria from reading itself or from reading too closely related wanted poster designs. When being used for gene editing, molecular biologists will design a wanted poster of their own and put it into the CRISPR/Cas9 system, but with a couple of tweaks to focus it on the desired DNA sequence. The encapsulated RNA and protein are injected into the target organism, where they are used to find and destroy the DNA. When the cell attempts to repair the double-strand break, it will use an introduced DNA sequence as a template for repair. When the CRISPR/Cas9 system locates the target sequence, the protein will bind and cleave the targeted sequence. Due to its simplicity, power, and precision, CRISPR/Cas9 has empowered researchers and large organizations to engineer genetic changes in mice, monkeys, and human cells. These changes—ranging from deletion or silencing of a specific gene to insertion of a gene bearing a variant allele or genetic material—hold tremendous therapeutic promise. But as the toolkit for engineering the genomes of living organisms has evolved, so has the risk of a doomsday bug or infotech nightmare looming over humanity.